ChemInform Abstract: Sesquiterpenes from Carpesium macrocephalum Inhibit Candida albicans Biofilm Formation and Dimorphism. Issue 11 (February 2016) - Xie, Chunfeng; Sun, Lingmei; Meng, Linghao; Wang, Meicheng; Xu, Jing; Bartlam, Mark; Guo, Yuanqiang
Abstract: 4‐(2‐Methylbutyryl)‐4H‐tomentosin (I), a new xanthanolide from the whole plant of Carpesium macrocephalum, is isolated along with nine known sesquiterpenes.